The reality of bee breeding in Iraq and ways to develop it - مجيد عمر حميد (Journal of Economics and Administrative Sciences, 2011)
This study was (the reality of beekeeping in Iraq and ways of developing them) as a research project in the branch of production is important branches of the productivity of the agricultural sector in Iraq, and the importance of this section, productive (beekeeping) for the agricultural sector in his contribution to increase the vegetable production and improve the quality and the various Classes of types, through its active role in the pollination of plants and indirectly (when the bees to move between plants to collect nectar and pollen grains), which contributes to reduce the losses in plant production and raise the rate of productivity per donum of various agricultural crops. On the other hand play a beekeeping a significant role in contributing to agricultural production, and then GDP through what is produced along with natural honey products are many and varied and useful such as (the royal food, stinging bee, bees boxes, wax natural, pollen), as show that beekeeping in Iraq contributed approximately (53) billion dinars in the GDP for the year (2007) for only three products are (natural honey, bees boxes, wax natural). To learn the benefits of beekeeping numerous and large and how to use them in Iraq in order to develop the agricultural sector and support the agricultural development process in which, therefore, been divided this research into four main parts deal with the first, the importance of beekeeping in Iraq, it included nine benefits and important benefits to beekeeping, and the second description and analysis of the characteristics and attributes of beekeeping in Iraq, based on the available statistical data on beekeeping in Iraq, while the third addressed the constraints of beekeeping in Iraq, and included on the environmental constraints and obstacles to support and constraints of pests and diseases of bees and marketing constraints and constraints of human, while addressing Part fourth and the latter the most important actions to be taken for the development of beekeeping in Iraq, as was emphasized in this section are all that would develop and the development of beekeeping in Iraq and increase productivity.